Training of Trainers (ToT) on Enhancing National Climate Services (ENACTS) Maprooms for Users in Kenya - Grossi, Amanda; Dinku, Tufa (Accelerating Impacts of CGIAR Climate Research for Africa, 2022)
A five-day training of trainers (ToT) workshop was implemented from October 31 to November 4, 2022, in Nairobi, Kenya by the International Research Institute for Climate and Society (IRI) in collaboration with the Kenya Meteorological Department (KMD) and the International Livestock Research Institute (ILRI). The workshop, which was organized as part of the World Bank’s Accelerating the Impact of CGIAR Climate Research for Africa (AICCRA) project, brought together 21 participants from national and county KMD offices, the Ministry of Agriculture, Livestock, and Fisheries (MOAL&F), and the Kenya Agriculture and Livestock Research Organization (KALRO) to be trained on KMD’s existing suite of free online ENACTS Maprooms. The major objective of the workshop was to ensure that each of these institutions that play an important role in promoting the use of climate information and services and broader resilience of the agricultural sector are aware of and have the capacity to train users within Kenya on the best-available climate information products for decision-making. The ENACTS maproom products, which are freely available through KMD’s website, provide location-specific (4 km grid) historical, monitoring, and forecast information that is important for activities related to planning, monitoring, and response for the agricultural sector and wider food system.